Treatments of meniscus lesions of the knee: current concepts and future perspectives - Cengiz, I. F. (2017)
The present preference in the clinical management of meniscus lesions is to preserve it by repairing whenever possible or substituting the tissue. Still, meniscectomy continues to be one of the most frequent orthopedic procedures regardless of the fact that it may lead to a series of early degenerative events in the knee. Surgical and technological advances enabled to extend the indications for meniscus repair. The outcome of meniscus repair is influenced by several factors. Classification of meniscus lesions remains a challenge while there have been some attempts in building consensus around it. Substitution of meniscus tissue has been performed to avoid or minimize the possible degenerative effects occurring in the absence of meniscus. Meniscus allograft transplantation has demonstrated its use as a replacement strategy of large lesions. In partial lesions, the use of acellular scaffolds has provided an improved clinical outcome when the insertional horns and the peripheral rim are preserved. However, the current scaffolds have shown some limitations, and the neotissue is different from the native meniscus. Tissue engineers thus envision going beyond the partial meniscus regeneration. Nowadays, it is aimed to develop a new generation of meniscal implants for total meniscus regeneration, which not only meet the biomechanical requirements but also the biological requirements both in the short- and long-term. Moreover, these might be patient/injury-specific regarding the size and shape as well as being cultivated with autologous cells and biologically enhanced. Herein, the clinical management of meniscus lesions and advanced tissue engineering strategies are reviewed.